COMMUNITY STRUCTURE GASTROPOD DAN BIVALVE (MOLLUSCS) IN THE TERKUL COASTEL AREA OF RUPAT BENGKALIS DISTRICT - Apriyani, Apriyani; Mulyadi, Aras; Nasution, Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Gastropods and Bivalves are two important classes of molluscs living on the Terkul coastal area. Species of these class are often used by local people for livestock feed, handicraft materials and was consumed. This study aimed to determine the structure of community Gastropods and Bivalves in coastal areas of Terkul Rupat Bengkalis Regency. This research was conducted in February - May 2018. Sample collection of Gastropods and Bivalves taken from on 4 certain stations using quantitative and qualitative methods.From this research were found 17 species, consisting of 13 species of Gastropods and 4 species of Bivalves. The highest density of Gastropods is in Station III of 10.67 ind / m2 with characteristics ie near the Terkul port and mangrove grow rarely. The value of Diversity (H ') is high, ranging from 2.26 to 3.13, the uniformity value (E) is in the range of 0.43 to 0.59, the dominance value (C) ranges from 0.13 to 0.43. The distribution pattern of 12 species is clumped and 1 species is uniform. The highest bivalves density is at station III of 0.56 ind / m2 with characteristics ie near the Terkul port and mangrove grow rarely. The value of diversity (H ') is, ranging from 0 to 1.52, uniformity value (E) is ranging from 0 to 0.75, the dominance value (C) ranges from 0 to 0.37. The pattern of distribution of 3 species are uniform and 1 species clumped. Keywords: Community structure, Pulau Rupat, Gastropod, Bivalve.